Badges of Social Valuing and the Biography. Natalia’s Interview in the Perspective of Sociologist of Poverty and Social Exclusion - Golczyńska-Grondas, Agnieszka (Qualitative Sociology Review, 2014)
The paper presents an attempt to analyze the interview with Natalia within the framework of sociology of poverty and from a social exclusion perspective. The information about the origins of Natalia’s interview is delineated. In the main part of the text, the author refers to the concept of the badge of ability, described by Richard Sennett and Jonathan Cobb, as a tool of social categorizing and valuing and introduces the corresponding notion of the badge of inability, ascribed to the unprivileged group members. Furthermore, the influence of both kinds of badges on the situation of Natalia’s family of origin, on her life course, and self-description are indicated with some remarks on the narrator’s biographical and identity work. The last part of the paper presents the narrator’s understanding of the world of poverty and social exclusion, its mechanisms, and conditionings.